A(2, 7), B(4, -1), C(-2, 6) AB = √ (4 + 64) = √ 68 BC = √ (36 + 49) = √ 85 AC = √ (16+1) = √ 17 We see that AB² + AC² = BC² (follows Pythagoras theorem) ⇒ The triangle is a right triangle at A(2, 7).
An adiabatic process is one in which the:
Which of the following is not the desirable characteristics in Film-forming type anti-transpirants
Fresh milk contain what % of water?
In active packaging Potassium permanganate act as….
Cell is the fundamental structural and functional unit of all living organisms. It was first discovered by ____
In reduction reaction what happens?
I n the new initiative called "Hariyali," how are the area development programmes to be implemented under the National Watershed Development Programme?
Which of the following correctly defines the "RotoDynamic Pumps"
What is the correct definition of "Economic Injury Level (EIL)"?
The light intensity at which photosynthesis and respiration are equal is called